Syria and the Chemical Weapons Taboo. Issue 1 (20th February 2019) - Price, Richard
Abstract: Has the use of chemical weapons (CW) in Syria eroded the CW taboo? In this article I argue that, despite the significant violations of the CW taboo in the Syrian conflict, the trend overall is not indicative of the erosion of the long-standing international norm that prohibits the use of chemical weapons in warfare. I consider evidence that supports but could also challenge such an assessment, drawing upon indicators for norm robustness and erosion, including the nature of the violations, reactions to violations by third parties, concordance in belief and practice, and implementation and institutionalization.